2020
DOI: 10.1002/ange.202006729
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen‐Doped Carbon‐Assisted One‐pot Tandem Reaction for Vinyl Chloride Production via Ethylene Oxychlorination

Abstract: Abifunctional catalyst comprising CuCl 2 /Al 2 O 3 and nitrogen-doped carbon was developed for an efficient one-pot ethylene oxychlorination process to produce vinyl chloride monomer (VCM) up to 76 %y ield at 250 8 8Ca nd under ambient pressure,whichishigher than the conventional industrial two-step process (% 50 %) in as ingle pass.Int he second bed, active sites containing N-functional groups on the metal-free N-doped carbon catalyzed both ethylene oxychlorinationa nd ethylene dichloride (EDC) dehydrochlorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The tandem reactions catalyzed by functional nanostructures have been effectively studied. [34][35][36][37] Typically, tandem reactions occur on the multifunctional material surfaces or at the interface of different function materials. 34,38 Our previous mechanism studies of tandem reactions found the spatial arrangement of the interfaces of tandem catalyst could control the generation, diffusion and reaction of the intermediates and finally favor the selectivity of desired products.…”
Section: Introductionmentioning
confidence: 99%
“…The tandem reactions catalyzed by functional nanostructures have been effectively studied. [34][35][36][37] Typically, tandem reactions occur on the multifunctional material surfaces or at the interface of different function materials. 34,38 Our previous mechanism studies of tandem reactions found the spatial arrangement of the interfaces of tandem catalyst could control the generation, diffusion and reaction of the intermediates and finally favor the selectivity of desired products.…”
Section: Introductionmentioning
confidence: 99%